1990
DOI: 10.1002/j.1552-4604.1990.tb03460.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Therapeutic Effects and Dosage Equivalence of Glyburide and Glipizide

Abstract: Nineteen noninsulin-dependent diabetic patients [ten women, nine men, aged 36-80 years (mean +/- SE 56.8 +/- 2.7 years)] were randomized to receive either glyburide or glipizide for 16 weeks, in a double-blind crossover fashion. A 2-week washout period preceded each treatment period. The patients measured blood glucose concentrations 16 times weekly using Chemstrip-bG. The medication dosages were titrated to achieve fasting blood glucose concentrations of less than or equal to 6.2 mM and preprandial and postpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This assumption since has been questioned by some authors (14,15), who suggested that GB is nearly twice as potent as GP. Within the limits of our study, the assumption of approximate equipotency of GP and GB on a weight basis appears reasonable, although we would stress that the study was not specifically designed to address this issue, and that dose titration was not performed during the study.…”
Section: Conclusion-mentioning
confidence: 96%
“…This assumption since has been questioned by some authors (14,15), who suggested that GB is nearly twice as potent as GP. Within the limits of our study, the assumption of approximate equipotency of GP and GB on a weight basis appears reasonable, although we would stress that the study was not specifically designed to address this issue, and that dose titration was not performed during the study.…”
Section: Conclusion-mentioning
confidence: 96%
“…The primary mechanism is stimulation of insulin secretion (1)(2)(3)(4)(5), but insulin sensitivity may also be enhanced (6)(7)(8)(9)(10)(11)(12)(13). The clinical efficacy of the two second generation SUs glipizide and glyburide has been compared in several studies (8,(14)(15)(16)(17)(18)(19)(20)(21)(22). However, few studies have been doubleblind and placebo-controlled, and many have used doses higher than recommended, at least in Europe.…”
mentioning
confidence: 98%